Isolation of Viable Follicles from Cryopreserved Human Ovarian Tissue - Farnaz Tajbakhsh; Somayeh Tavana; Mohammad Kazemi Ashtiani; Naeimeh Sadat Abtahi; Leila Sadat Tahaei; Ashraf Moini; Rouhollah Fathi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Ovarian tissue freezing is the most effective method to maintain fertility for immature girls and women diagnosed with cancer. Nonetheless, because of the chance that malignant cells might reappearing following tissue transplantation, it is crucial to isolate the follicles from the frozen-thawed ovarian tissue of these individuals and employ them in the process of in vitro maturation process or artificial ovarian framework. This study aimed to assess the application of neutral red (NR) vital dye alongside collagenase IA for effectively isolating viable follicles from the vitrified human ovarian tissue samples. Methods: Two categories existed: the category with NR and the group without NR. Chopped (0.5×0.5 mm) strips of vitrified-warmed ovarian tissue from 10 transsexual individuals were placed into two falcon tubes with HTCM and Collagenase IA (1mg/ml). Neutral red (NR) was introduced to one of the falcons. Follicles were then isolated mechanically. The morphology, size, and viability of the follicles were assessed. The condition of the follicles was evaluated using fluorescent staining methods involving Calcein-AM and Ethidium homodimer-I. The t-test method was used to evaluate the data. Results: The number of isolated follicles with Neutral Red (46.50±25/02) exceeded those without NR (6.6±5.58; P < 0/0001). Additionally, according to the morphological studies, a majority of the isolated follicles from the transsexual ovarian cortex were primordial (77.4%), and primary (21.12%) follicles, with only a small number of secondary follicles (1.4%) identified in these tissues. Live/dead staining verified the viability of isolated follicles by displaying a green hue. Conclusion: The finding indicates that combining collagenase I with the vital dye Neutral red significantly facilitates the of follicles from dense human ovarian tissue.